Decision Support System for New Employee Selection at PT Selalu Cinta Indonesia through the Analytical Hierarchy Process (AHP) Method - Tunikmah, Esti Azizah; Wibowo, Agung (PT Mattawang Mediatama Solution, 2023)
Managing human resources holds significant importance within a company, as it anticipates each employee’s effective contribution to fulfilling organizational responsibilities. A decision support system is required to avoid decisions made subjectively. This system is able to help management in selecting the right employees for the company. The existence of this system allows companies to process applicant data quickly, which helps make decisions about recruiting new employees. This decision support system utilized the Analytical Hierarchy Process method (AHP), which can help decision makers in a complex manner. The AHP method sets priorities in a structured process (hierarchy) that comes from decomposed criteria or structure.